Attenuation and vaccine potential of aroQ mutants of Corynebacterium pseudotuberculosis - Simmons, Cameron (2018)
Corynebacterium pseudotuberculosis, a gram-positive intracellular bacterial pathogen, is the etiological agent of the disease caseous lymphadenitis (CLA) in both sheep and goats. Attenuated mutants of C. pseudotuberculosis have the potential to act as novel live veterinary vaccine vectors. We have cloned and sequenced the aroB and aroQ genes from C. pseudotuberculosis C231. By allelic exchange, aroQ mutants of both C231, designated CS100, and a pld mutant strain TB521, designated CS200, were constructed. Infection of BALB/c mice indicated that introduction of the aroQ mutation into C231 and TB521 attenuated both strains. In sublethally infected BALB/c mice, both CS100 and CS200 were cleared from spleens and livers by day 8 postinfection. The in vivo persistence of these strains was increased when the intact aroQ gene was supplied on a plasmid in trans. Mice infected with TB521 harbored bacteria in organs at least till day 8 postinfection without ill effect. When used as a vaccine, only the maximum tolerated dose of CS100 had the capacity to protect mice from homologous challenge. Vaccination with TB521 also elicited protective immunity, and this was associated with gamma interferon (IFN-gamma) production from splenocytes stimulated 7 days postvaccination. The role of IFN-gamma in controlling primary infections with C. pseudotuberculosis was examined in mice deficient for the IFN-gamma receptor (IFN-gammaR(-/-) mice). IFN-gammaR(-/-) mice cleared an infection with CS100 but were significantly more susceptible than control littermates to infection with C231 or TB521. These studies support an important role for IFN-gamma in control of primary C. pseudotuberculosis infections and indicate that aroQ mutants remain attenuated even in immunocompromised animals. This is the first report of an aroQ mutant of a bacterial pathogen, and the results may have implications for the construction of aromatic mutants of Mycobacterium tuberculosis for use as vaccines.